A case study exploring if a behaviour change intervention can increase adherence to athlete monitoring - Neupert, E.; Holder, T.; Jobson, S. A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Athlete monitoring is used to inform training programming, to optimise performance and to minimise the risk of athlete maladaptation. This is particularly important in elite sport where the high training loads and limited recovery periods increase the risk of negative performance and health outcomes. Poor athlete buy-in to monitoring has been recognised as a significant barrier to athlete monitoring system (AMS) implementation (1). However, the application of any systematic approach to combat poor buy-in to monitoring is notably absent from research. This study therefore aims to assess if a behavioural change intervention can remedy poor AMS adherence (2).